دراسة انتشار أضداد التهاب الكبد د لدى مرضى التهاب الكبد ب المزمن - يازجي, هيثم; زيزفون, حسان; مرسل, ندى (Latakia University Journal -Medical Sciences Series, 2018)
أشارت العديد من الدراسات و التقارير إلى انتشار فيروس التهاب الكبد د في مناطق عديدة من العالم بنسب مختلفة ,تتراوح بين مناطق وبائية و مناطق ذات انتشار منخفض . و للوقت الحالي لا تتواجد دراسة منشورة في سوريا تبين لنا نسبة انتشار هذا الفيروس بين مرضى التهاب الكبد ب المزمن .لذلك كان الهدف من هذا البحث معرفة معدل انتشار فيروس التهاب الكبد د لدى مرضى التهاب الكبد ب المزمن و ذلك لاتخاذ الاجراءات المناسبة في معالجة هؤلاء المرضى و ذلك نظرا لزيادة خطورة المرض الكبدي في حالة الاصابة به .77مريض بالتهاب الكبد ب المزمن و المؤكد بتحاليل سلسلة البوليمراز PCR 25 من النساء و 52 من الرجال من مراجعي مركز التهاب الكبد في مديرية صحة اللاذقية خضعوا لتحري أضداد فيروس د بتقنية ELISA فكانت النتائج تشير الى ايجابية الاضداد لدى ثلاثة مرضى ( امرأة و رجلان ) فكانت نسبة الانتشار تقدر ب 3.7 %من المرضى .مما يشير إلى نسبة انتشار متوسطة للفيروس مقارنة مع الدراسات المنشورة في دول الجوار .Several studies and reports have indicated the prevalence of hepatitis D virus infection in many parts of the world at different rates , Ranging from areas of epidemiological and areas with a low prevalence of it.Till now there is no study in Syria shows us the prevalence of viruse Delta in chronic hepatitis B patients .The aim of our study was to determine the current prevalence of hepatitis D in chronic hepatitis B patients . And to take appropriate measures in dealing with these patients due to the increased risk of liver disease in the event of injury by it .77 patients with chronic hepatitis B certainly proved with PCR analysis 25 women and 52 men visiting the center of hepatitis in Latakia were tested for antibody to hepatitis D virus (anti-HDV) by ELISA test .The results indicate a positive antibody in three patients (women and 2 men) and the prevalence was 3.8% , which point to a moderate prevalence of hepatitis D comparing with neighboring countries.